1998
DOI: 10.1038/bjc.1998.448
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay of epidermal growth factor receptor in lung cancer: comparisons with immunohistochemistry, clinicopathological features and prognosis

Abstract: Summary The prognostic role of epidermal growth factor receptor (EGFR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In the literature, there is a disagreement about prognostic significance of EGFR expression in NSCLC patients. In most studies, EGFR expression was not correlated with patients' survival [20,22,23,30,32,33]. However, some authors found EGFR overexpression as a positive [34] and some as a negative [24] factor influencing patients' survival.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the literature, there is a disagreement about prognostic significance of EGFR expression in NSCLC patients. In most studies, EGFR expression was not correlated with patients' survival [20,22,23,30,32,33]. However, some authors found EGFR overexpression as a positive [34] and some as a negative [24] factor influencing patients' survival.…”
Section: Discussionmentioning
confidence: 96%
“…For example, data on the significance of tumour proliferation rate in NSCLC are controversial [15][16][17][18][19]. The same is true about the epidermal growth factor (EGF) [20][21][22][23][24]. It has become apparent that cancer cells are able to produce and respond to their own growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ELISA technique is less used in clinical study, this method is also widely accepted to determine protein expression levels. Examples include using this technique in the studies of breast cancer, cervical cancer, lung cancer as well as head and neck cancer (Christensen et al, 1995;Pfeiffer et al, 1998;Contreras et al, 2002;Widschwendter et al, 2002). The key advantage of the ELISA method is to provide a quantitative result with relatively less bias.…”
Section: Discussionmentioning
confidence: 99%
“…The key advantage of the ELISA method is to provide a quantitative result with relatively less bias. When comparing these two methods, Pfeiffer et al (1998) have reported that significant correlation was found in the quantification of EGFR or Her-2 levels between ELISA and immunohistochemical methods studied in the lung and in breast cancers. These studies suggest that comparable evaluation results may be obtained by using these two assay techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, total EGFR expression rarely relates to other clinical prognostic indicators in NSCLC [10]. Only 3 of 10 published studies have shown an association between EGFR expression and either relapse-free or overall survival rates [11][12][13][14][15][16][17][18][19][20]. Importantly studies have shown that total EGFR expression does not correlate with clinical response to tyrosine kinase inhibitors like gefitinib or erlotinib [21] suggesting other characteristics of EGFR beside expression level are important to the response.…”
Section: Introductionmentioning
confidence: 99%